COMPARISON TRADITIONAL FOLKLORE BETWEEN CHINESE PI YING AND INDONESIAN WAYANG KULIT - Guannan, Zhang (UI Scholars Hub, 2020)
Chinese Pi Ying and Indonesian Wayang Kulit as known as the crystal of folklore from two different countries. This article is aim to make a comparison between these two traditional folklore. Pi Ying and Wayang Kulit both are made from wood and paper or animal skin. The function of these two folklore is giving a show or performance to audiences based on traditional stories or mythological stories. Compared with Wayang Kulit, Chinese Pi Ying was originated from Han Dynasty, earlier than Wayang Kulit. As traditional arts, coming with improvement of digital technology, Chinese Pi Ying and Wayang Kulit are losing their influence now, these two traditional folklore only can be seen more frequently in theater or rural area. Through this article, Pi Ying and Wayang Kulit will be analyzed, compared and found out the same and different aspects from these two traditional folklore, furthermore, this article will also give certain solutions to solve the problems these two folklore are facing.